Forgotten Master: Leone Giraldoni and the Pursuit of Singing Artistry - (:unkn) unknown (My University, 2011)
The Italian baritone Leone Giraldoni (1824-1897) was one of the most prominent operatic performers of the nineteenth century. His singing style and complete artistry made him a leading choice of the major opera composers of his day, not the least being Giuseppe Verdi, for whom he created Renato in Un Ballo in Maschera (1859) and the title role in Simon Boccanegra (1857). At the height of his talents, Giraldoni was regarded with great esteem throughout Europe and England. Toward the end of his singing career, Giraldoni also gained a reputation as a celebrated teacher throughout France, Italy, Spain and Russia, where he taught at the Moscow Conservatory. The purpose of this document is to make available in English translation for the first time one of two treatises that he wrote regarding the training of the singing artist, Guida teorico-pratica ad uso dell'artista-cantante, written in 1864 with an expanded and revised version in 1884. The document will also examine the teaching approach of the old Italian school of singing through a commentary and discussion of the content of the treatise, with reference to both old and modern works on singing and information gathered from biographical accounts of Giraldoni's contemporaries.
Keywords: Singers--Biography; Voice culture; Singing--Instruction and study